Wideband Tympanometry and Pressurized Otoacoustic Emissions in Children with Surgical Excision of Palatine and/or Pharyngeal Tonsils - Aline Buratti Sanches; Milaine Dominici Sanfins; Piotr Henryk Skarzynski; Magdalena Beata Skarżyńska; Henrique Costa Penatti; Caroline Donadon; Ingrid Pereira de Souza; Ingridy Vitoria da Silva; Maria Francisca Colella-Santos (Brain Sciences, 2024)
Palatine and pharyngeal tonsil hypertrophy may lead to dysfunction of the auditory tube due to a propensity for infection, potentially giving rise to otitis media. This is a quantitative and longitudinal study, developed from 2019 to 2021, at the State University of Campinas (UNICAMP). The studied sample comprised 15 participants aged 5 to 12 years (mean 7.9 years), 12 male and 3 female, arranged into two groups: children diagnosed with pharyngeal and/or palatine tonsil hypertrophy who were candidates for surgery (G1), and children who were later evaluated after surgery (G2). As part of the test, an otoscopy and measurements of logoaudiometry, pure-tone threshold audiometry, wideband tympanometry (ambient and peak pressure), and otoacoustic emissions (TEOAEs and DPOAEs, both at ambient and peak pressure) were all performed. There were statistically significant differences between phases in pure-tone audiometry, in terms of 226 Hz tympanometry, wideband tympanometry in peak pressure conditions, in the amplitude measurement TEOAEs in both pressure conditions, in DPOAEs in ambient pressure conditions, and in the signal/noise measurement in both pressures in DPOAEs. Overall, it was found that hearing tests were different for subjects with palatine and pharyngeal tonsil hypertrophy compared to the post-surgical group.